GWAS-significant loci and severe COVID-19: analysis of associations, link with thromboinflammation syndrome, gene-gene, and gene-environmental interactions - Loktionov, Alexey Valerevich; Kobzeva, Ksenia Andreevna; Karpenko, Andrey Romanovich; Sergeeva, Vera Alexeevna; Orlov, Yuriy Lvovich; Bushueva, Olga Yurievna (Frontiers in Genetics, 2024)
The aim of this study was to replicate associations of GWAS-significant loci with severe COVID-19 in the population of Central Russia, to investigate associations of the SNPs with thromboinflammation parameters, to analyze gene-gene and gene-environmental interactions.Materials and methods: DNA samples from 798 unrelated Caucasian subjects from Central Russia (199 hospitalized COVID-19 patients and 599 controls with a mild or asymptomatic course of COVID-19) were genotyped using probe-based PCR for 10 GWAS-significant SNPs: rs143334143